The role of angiopoietin-like 4 (ANGPTL4) in chemoresistance and autophangy during epithelial-mesenchymal transition (EMT) - Lim, Maegan Miang Kee (2019)
Patients with metastatic cancers often displayed multidrug resistance (MDR) and emerging studies have shown that the Angiopoietin-like 4 (ANGPTL4) protein plays critical roles in metastatic dissemination of cancer cells during epithelial-mesenchymal transition (EMT), an early stage event during cancer metastasis. Our studies demonstrated that ANGPTL4 confers MDR phenotype to metastatic cells via ATP-binding cassette (ABC) transporters expression and activities, as well as coordinating cellular bioenergetics and increasing cellular adenylate energy charge via regulation of glucose and lipid metabolism and autophagy to providing for energy demanding processes during EMT. This suggests that strategies to suppress ANGPTL4 expression and function, may provide a dynamic therapeutic intervention in overcoming MDR in metastatic cancers.